PARADOX OF TOLERATION - Fikret YILMAZ (Fırat University, 2019)
Toleration, which allows people to live together despite their differences, has paradoxes in itself. The concept of toleration is primarily a guide on how I should behave towards being not like me. It is clear that people are different; toleration preliminary accepts me and the other’s difference. Besides, the concept of toleration is an improved attitude towards intoleration. The emergence of the concept of tolerance is to get rid of the negative effects of toleration. However, it is noticed that toleration can not bring about the positive effects that it wants to reveal due to the intoleration which is the opposite of toleration within the process. The effects of the paradoxical structure can be seen here. In connection with any situation or situation, a person will tolerate a situation different from his or her own values or acceptance. In this case, the person will be able to make it worthless to himself or to move away from the life he / she accepts. As a result of tolerated subjects, there may not be a topic to be tolerated. Because, If the person, the group, the society, moving away from their own selves, they can accept what they have tolerated as their own truth. In addition to this, the question, “is there a limit to what I will tolerate” is on the agenda. Can intoleration be tolerated? Should I tolerate a crime committed against humanity, a nation, society, community? Toleration to intoleration will bring about disappearance of toleration. In this case it is unclear what will determine differance between toleration and intoleration. If I do not tolerate what is intolerant, the things that make me different from will come off spontaneously. Likewise, if I show toleration to intoleration, a structure will be formed against my loss and even toleration. In this case, I will have to set a limit on what I will tolerate. The paradoxical structure of the concept of tolerance still appears. Is it possible to determine this limit? Or how will the content of the border be determined? Is it always possible to keep the border the same? It is understood that it is very difficult to determine what this boundary is. First of all, it can be very difficult if the accepted limit applies to everyone. The culture, beliefs, philosophical views people belong to, the power relations they are in will be decisive about what the boundary should be. Furthermore, if a boundary is accepted and this boundary is not tight enough to prevent harm from social values, then the characteristics determine the quality of the society will be removed and there will be no situation where Intoleration will be shown. The values that sould be tolerated will become dominant values, in a sense, intoleration will be out of toleration. If this limit is rather limited and tight, the possibility of doing a tolerant behavior will be greatly reduced. Besides, is toleration an expression of superiority? The person who will show toleration has a more effective power than tolerated. Toleration appears to be a principle in determining the dominance / power relation in this sense. If toleration is determined according to dominance / power relation, the limit of it can be determined in relation to the interests of the stronger one. To see tolerated as weak, it may also bring to the agenda that it is defective, imperfect or faulty. Tolerance can then lead to intoleration. Ernesto Laclau (1935-2014) states that tolerantion is undecidability. Evaluating the concept of toleration in relation to intoleration, Laclau refers to the paradoxical nature of this concept. In this presentation, based on the paradoxical situations involved in toleration and the views of Ernosto Laclau and Habermas, an inquiry will be made on what the toleration is and is not.